Physical properties of a natural foam made from gambier: influence of proportion of gambier extract used - Inda Three Anova; Anwar Kasim; Tuty Anggraini (Institution for Industrial Research and Standardization of Industry - Padang, 2018)
Tannin made from gambier extract contains hydroxyl groups and so can be modified to synthesize polymers. Gambier extract has a high tannin content that contains polyflavonoids with other additives. This allows it to be modified by polycondensation to make a polymer foam which can be used as an insulator for heat and sound, an absorber of heavy metal pollutants and for protective packaging. This study investigates the utilization of gambier in the manufacture of foam and determines the physical properties of the foam produced. The study was conducted using ethanol to produce the gambier extract from leaves of the plant which was used in the proportions of 14%, 24%, and 34% by weight to make different foam samples. Foam produced from 24% gambier extract had optimum qualities with a density value of 0.34 g/cm3, pH 6.83, compressive strength of 0.14 kg/cm2, thermal conductivity of 5.52 W/moC, and was semi-flexible foam. AbstrakSalah satu senyawa kelompok OH yang dapat dimodifikasi untuk tujuan sintesis polimer adalah tanin dari ekstrak gambir. Ekstrak gambir dengan kandungan tanin tinggi dapat dimodifikasi untuk pembuatan busa yang dapat digunakan sebagai bahan isolator panas, suara, dan penyerap logam serta untuk pengemasan. Pada pembuatan busa berbasis gambir, tanin yang terdapat pada gambir berfungsi sebagai isolasi materi yang terjadi karena polikondensasi dari poliflavonoid tanin dengan bahan tambahan lainnya. Penelitian ini bertujuan untuk memanfaatkan gambir dalam pembuatan busa dan mengetahui sifat fisik busa yang dihasilkan. Penelitian dilakukan dengan tahap awal ekstraksi gambir menggunakan etanol. Perlakuan penelitian adalah pemakaian ekstrak gambir 14%, 24%, dan 34%. Hasil penelitian menunjukkan bahwa busa yang dihasilkan dari pemakaian ekstrak gambir 24% memiliki nilai densiti 0,34 g/cm3, pH 6,83, kuat tekan 0,14 kg/cm2, konduktivitas termal 5,52 W/moC, dan busa dapat digolongan sebagai busa semi fleksibel.